GINS1 is a prognostic biomarker and correlated with methylation and immune escape in liver hepatocellular carcinoma - Liang, Mingchao; Lai, Tianqi; Li, Zhen; Yu, Wei; Cao, Mingrong; Yao, Nan; Hu, Youzhu; Liu, Tongzheng; Liang, Junjie (Frontiers in Oncology, 2025)
GINS1 is correlated with a poor prognosis in numerous cancers including liver hepatocellular carcinoma (LIHC). Here, efforts have been made to explore the function and underlying mechanism in LIHC through bioinformatics analysis. The mRNA and protein expression data of GINS1 were downloaded from The Cancer Genome Atlas (TCGA) database, the Clinical Proteomic Tumor Analysis Consortium (CPTAC), the University of Alabama at Birmingham CANcer Data Analysis Portal (UALCAN), and the Human Protein Atlas (HPA) database. Moreover, the protein expression of GINS1 was further substantiated by immunohistochemistry staining from 116 clinical samples. Subsequently, the diagnostic and prognostic role of GINS1 in LIHC patients were determined using receiver operating characteristic (ROC) analysis and the Kaplan-Meier plotter (KM-plotter) database. GeneMANIA and STRING databases were respectively used to construct gene and protein-protein interaction (PPI) networks of GINS1. Enrichment analyses were conducted to investigate the functions of GINS1. To assess the genetic alterations, methylation, and prognostic value, cBioPortal, and MethSurv databases were utilized. Additionally, Tumor Immune Estimation Resource (TIMER), Tumor-Immune System Interaction Database (TISIDB), and Gene Expression Profiling Interactive Analysis (GEPIA) were used to explore the correlation with tumor immune. Differential expression analyses validated the upregulation of GINS1 in LIHC. Furthermore, the prognostic and diagnostic values of GINS1 were substantiated by the ROC curve, Kaplan-Meier plotters, and forest plots. Further enrichment, methylation, and tumor immune microenvironment analyses showed an intimate connection with GINS1. In conclusion, GINS1 which is correlated with methylation and immune escape may predict the prognosis of LIHC.